THE LEGAL STATUS OF ECOCIDE AS AN INTERNATIONAL CRIME - Dr. Parveen Gul; Bushra Zeb; Kainat (International Journal of Contemporary Issues in Social Sciences, 2024)
Severe and widespread destruction of the environment, or Ecocide, has become a hot-button global problem. Although there has been increasing awareness of environmental degradation, Ecocide is yet to become internationally recognized as a distinct crime. This research paper explores the legal status of Ecocide, considering its historical emergence, international legal status, and its advocacy to incorporate into the Rome Statute of the International Criminal Court. The research study addresses the problem of defining and enforcing Ecocide as an international crime using a comparative analysis of the domestic and international legal machinery. In addition, it explores how states, companies, and international organizations are dealing with environmental harm and the advantages of making Ecocide a crime. Ultimately, the study provides policy recommendations for strengthening global legal responses to Ecocide.